1989
DOI: 10.1002/1520-6629(198901)17:1<30::aid-jcop2290170105>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

PBB: An environmental contaminant in michigan

Abstract: The accidental introduction of the fire retardant polybrominated biphenyl (PBB) into the food chain of Michigan in 1973 provides an example of an insidious, slowly developing, and still continuing technological catastrophe. Hartsough's transactional model of natural disasters is utilized to provide a conceptual framework to describe the psychological effects of the PBB crisis. Following this model, the event (toxic chemicals within the food chain) led to the quarantine of 576 farms, destruction of millions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous CP research on environmental issues, especially on toxic waste and nuclear energy (e.g. Lounsbury et al 1979;Webb 1989;Rich et al 1995;Culley and Hughey 2008;Culley and Angelique 2011), and on the environmental movement (Dean and Bush 2007;Quimby and Angelique 2011) parallels research in environmental sociology.…”
Section: Towards a Stronger Link Between Humans And The Natural Envirmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous CP research on environmental issues, especially on toxic waste and nuclear energy (e.g. Lounsbury et al 1979;Webb 1989;Rich et al 1995;Culley and Hughey 2008;Culley and Angelique 2011), and on the environmental movement (Dean and Bush 2007;Quimby and Angelique 2011) parallels research in environmental sociology.…”
Section: Towards a Stronger Link Between Humans And The Natural Envirmentioning
confidence: 99%
“…This body of research has focused on three themes. The first theme is the dynamics of social power and the degree of citizen participation in community responses to local environmental hazards, such as toxic waste spills and nuclear power plants (Lounsbury et al 1979;Webb 1989;Rich et al 1995;Culley and Hughey 2008;Culley and Angelique 2011). These studies pointed to the need for genuine community involvement and citizen empowerment in environmental decision-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…Compounding the problem, most rural communities do not feel immediately threatened by a bioterrorist attack and are therefore less prepared 3 . One study found that only 20% of all hospitals have response plans for incidents involving chemical or biological weapons and that rural hospitals are only one third as likely as urban hospitals to possess such capacity 8 …”
Section: Rural America—vulnerability To Bioterrorismmentioning
confidence: 99%
“…Technological Disasters Webb (1989) describes the accidental introduction of the fire retardant polybrominated biphenyl (PBB) into the food chain of Michigan in 1973 as an example of an insidious, slowly developing, and continuing technological catastrophe. D. M. Hartsough's (Hartsough & Myers,1985) transactional model of natural disasters is utilized to provide a conceptual framework for the psychological effects of the PBB crisis.…”
Section: Dohertymentioning
confidence: 99%